Principal component analysis of breeding values for growth and reproductive traits and genetic association with adult size in beef cattle - Boligon, A. A.; Vicente, I. S.; Vaz, R. Z.; Campos, G. S.; Souza, F. R. P.; Carvalheiro, R. [UNESP]; Albuquerque, L. G. [UNESP] (Amer Soc Animal Science, 2016)
Principal component analysis was applied to evaluate the variability and relationships among univariate breeding values predicted for 9 weaning and yearling traits, as well as suggest functions of the traits that would promote a particular breeding objective. Phenotypic and pedigree information from 600,132 Nelore animals was used. Genetic parameters and breeding values were obtained from univariate analyses of birth to weaning weight gain; weaning to yearling weight gain; conformation, finishing precocity, and muscling scores at weaning and at yearling; and yearling scrotal circumference. The principal component mainly associated with maturity (precocious vs. late animals) was used as a pseudophenotype in bivariate analyses with either adult weight or adult height of cows. Direct heritability estimates ranging from 0.19 +/- 0.01 to 0.41 +/- 0.01 indicate that these 9 traits are all heritable to varying degrees. Correlations between the breeding values for the various traits ranged from 0.14 to 0.88. Principal component analysis was performed on the standardized breeding values. The first 3 principal components attained the Kaiser criterion, retaining 48.06%, 18.03%, and 12.97% of the total breeding value variance, respectively. The first component was characterized by positive coefficients for all traits. The second component contrasted weaning traits with yearling traits. The third component represented a contrast between late maturity animals (better for weight gain and conformation) and early maturity animals (better for finishing precocity, muscling, and scrotal circumference). Thus, the first 3 components represent 3 different potential selection criteria. Selecting for the first principal component would identify animals with positive breeding values for all studied traits. The second principal component may be used to identify animals with higher or lower maturation rates (precocity). Animals with negative values in the third principal component are regarded as early maturing. Genetic correlations between maturity (third principal component) with adult weight and adult height were 0.19 +/- 0.02 and 0.32 +/- 0.02, respectively. These results showed that the weaning and yearling bovine maturity is genetically associated with the adult size of the cows used in reproduction.
Keywords: multivariate analysis; Nelore cattle; scrotal circumference; visual scores; weight gain